An Interstitial 4q Deletion with a Mosaic Complementary Ring Chromosome in a Child with Dysmorphism, Linear Skin Pigmentation, and Hepatomegaly. (27th July 2017) - Carter, J.; Brittain, H.; Morrogh, D.; Lench, N.; Waters, J. J.
Abstract : Interstitial deletions of 4q are rarely reported, vary in size, and have limited genotype-phenotype correlations. Here, genome-wide array CGH analysis identified a 21.6 Mb region of copy number loss at 4q12-q21.1 in a patient diagnosed with dysmorphism, linear skin pigmentation, and hepatomegaly. An additional small ring chromosome was detected in 5/30 cells examined via G-banding. Confirmation of the origin of the ring chromosome was obtained by FISH analysis which identified that the ring chromosome contained material from the deleted region of chromosome 4 and was therefore complementary to the 21.6 Mb deletion. Further microarray studies in the proband using a different microarray platform showed no evidence of mosaicism. This case highlights the importance of an integrated approach to cytogenetic analysis and demonstrates the value of G-banding for detecting mosaicism, as current microarray platforms are unable to detect low level mosaics.